Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1039/c8ta11378e
|View full text |Cite
|
Sign up to set email alerts
|

Flexible nonfullerene organic solar cells based on embedded silver nanowires with an efficiency up to 11.6%

Abstract: Flexible non-fullerene organic solar cells based on AgNWs embedded in polyimide substrates demonstrate a high efficiency up to 11.6%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(62 citation statements)
references
References 59 publications
2
60
0
Order By: Relevance
“…When the D/A ratio is 2:3 in the first coating, the device performance shows 11.40% PCE. Further decreasing the D/A ratio to 1:2 in the first coating improved the performance of device PCE with the maximum PCE of 12.29%, which is very close to that of the spin‐coated device …”
Section: Resultssupporting
confidence: 62%
“…When the D/A ratio is 2:3 in the first coating, the device performance shows 11.40% PCE. Further decreasing the D/A ratio to 1:2 in the first coating improved the performance of device PCE with the maximum PCE of 12.29%, which is very close to that of the spin‐coated device …”
Section: Resultssupporting
confidence: 62%
“…[ 23 ] Although AgNWs demonstrate many outstanding properties, to date, considerable efforts have mostly been devoted to the incorporation as transparent bottom electrodes to replace indium tin oxide (ITO) for highly efficient OPVs with reflective top electrode. [ 24–29 ] It was found that postprocessing treatments, such as high‐temperature thermal annealing (200 °C for 10–30 min), mechanical pressing, and so on, are usually required to reduce the contact resistance between the nanowires and hence achieve a desired electrical conductivity. Obviously, these treatments limit AgNWs in applications where it is used as the top electrode, especially for the devices that contain heat‐sensitive semiconducting materials, where postprocessing temperature can critically and negatively impact a carefully created and optimized morphology.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23,24 ] This factor has restricted the use of ITO as transparent electrodes in flexible solar cells. [ 25–29 ] Several ITO alternatives as FTEs have been studied over the years, including silver nanowires (Ag NWs), [ 30–32 ] conducting polymers, [ 33–41 ] carbon‐based materials (graphene and carbon nanotubes), [ 18,42–45 ] and many more. [ 46–48 ] Among them, poly(3,4‐ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) as transparent conducting polymers showed the most promising potential for cost‐effective flexible devices owing to its exceptional intrinsic flexibility, high transparency, easy film‐processability, and superior thermal stability.…”
Section: Figurementioning
confidence: 99%